#TITLE_ALTERNATIVE# - HASANUDIN SIDIK (NIM : 10211060), NATAADRIYA
Echocardiography is something very useful for the process diagnosis of heart disease and blood vessels, which utilize ultrasound waves to measure the velocity of blood flow in the artery and aorta. The sound waves echo recaptured by the transducer cause of the difference in frequency between the source and the receiver, the phenomenon known as the Doppler effect. In this research, we conducted a simulation and data collection on the 6 samples by applying echocardiography examination to measure blood flow velocity indices manually and automatic of the carotid artery. Research was done by providing the transducer frequency variations and variations in the Doppler angle, so that the observed relationship and influence between the Doppler angle, frequency transducer and an index of blood velocity. Testing is done by using statistical test (one way anova and correlation). From the tests, it was resulted that obtained showed a correlation between the frequency of the transducer and the Doppler angle to the value of relative velocity index in carotid arterial blood flow. In the result of experiment statistically, based on result one-way Anova showed there was different average Peak Systolic Velocity (PSV) and End Diastolic Velocity (EDV) either manually and automatic toward angle of variation, which showed on sig < 0,05, whereas the opposite is indicated on frequency variation with sig > 0,05. The result of correlation showed there was inverse relation between variation of frequency toward velocity of blood flow index, whereas the strongest relation showed by angle variation toward PSV and EDV, next relation about it can be observed by graphic. Concluded, there was significant influences from angle variation toward PSV and EDV, on the angle variation > 60 showed there was abnormal measuring, angle and frequency optimum in this research was angle between 30 - 60 with frequency 6,6 MHz. These results showed compatibility to the references.